2022
DOI: 10.1007/s10926-021-10019-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Employer Perspectives on Their Supportive Role in Accommodating Workers with Disabilities to Promote Sustainable RTW: A Qualitative Study

Abstract: Purpose Employers play an important role in facilitating sustainable return to work (RTW) by workers with disabilities. The aim of this qualitative study was to explore how employers who were successful in retaining workers with disabilities at work fulfilled their supportive role, and which facilitators were essential to support these workers throughout the RTW process. Methods We conducted a semi-structured interview study among 27 employers who had experience in retaining workers with disabilities within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These findings empirically establish the nomological proximity between managerial appraisals of RA implementation complexity and their attitudes toward EWD, and in doing so, contribute to a body of literature that has focused on linking broad disability support practices to outcomes for PwD (e.g. Gould et al ., 2022; Jansen et al ., 2022). Specifically, our study suggests that a finer analysis of managerial views of RA processes could help explain and connect the effectiveness of disability support initiatives, PwD experiences of the organisation and employment outcomes for this group (Bonaccio et al ., 2019; Cavanagh et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings empirically establish the nomological proximity between managerial appraisals of RA implementation complexity and their attitudes toward EWD, and in doing so, contribute to a body of literature that has focused on linking broad disability support practices to outcomes for PwD (e.g. Gould et al ., 2022; Jansen et al ., 2022). Specifically, our study suggests that a finer analysis of managerial views of RA processes could help explain and connect the effectiveness of disability support initiatives, PwD experiences of the organisation and employment outcomes for this group (Bonaccio et al ., 2019; Cavanagh et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Disability at work remains an under-investigated domain within organisational diversity research (Gould et al ., 2022), but a growing body of literature has made substantive contributions to our understanding of PwD experiences at work and of the effectiveness of diversity and inclusion (D&I) initiatives, including RA. This research has developed primarily around three main themes: (a) the lived experiences of PwD, spanning ableism, workplace relationships and employment outcomes (Carr and Namkung, 2021; Grześkowiak et al ., 2021; Lindsay et al ., 2022), (b) PwD views of the RA process and outcomes and the factors that influence their decision to disclose disability (Brzykcy and Boehm, 2022; Dong et al ., 2021; Kulkarni, 2022) and (c) disability support and inclusion practices in organisations (Gould et al ., 2022; Jansen et al ., 2022; Kwan, 2021). Yet, less is known about managerial attitudes toward hiring PwD, specifically how RA processes influence these attitudes, which has been noted as a significant gap in the literature (Bonaccio et al ., 2019; Cavanagh et al ., 2017; Suresh and Dyaram, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The (lack of) findings regarding factors more specifically related to the work situation were not expected since the intervention group received the DAP intervention, supposedly targeting a successful RTW process. The DAP intervention actively involves the manager of the individual with chronic pain in the RTW process [ 31 ], and a good relationship and collaboration between the manager and the employee has previously been highlighted as important for a successful RTW [ 25 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In two recent studies of ours, investigating the patient’s perspective [ 51 ] and the manager’s perspective (not yet published) when participating in the DAP, we found that the intervention was perceived to promote their relationship and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…The DAP intervention actively involves the manager of the individual with chronic pain in the RTW process [ 31 ], and a good relationship and collaboration between the manager and the employee has previously been highlighted as important for a successful RTW [ 25 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In two recent studies of ours, investigating the patient’s perspective [ 51 ] and the manager’s perspective (not yet published) when participating in the DAP, we found that the intervention was perceived to promote their relationship and collaboration. The participants in these two qualitative studies (in particular, the managers) further expressed that they believed the DAP intervention would benefit from including more than one meeting to follow up on the RTW process.…”
Section: Discussionmentioning
confidence: 99%
“…Workers can use self-regulatory processes to adjust their day-to-day work and schedules to overcome intermittent symptoms only if adequate leeway is available based on job demands and employer policies [ 6 ]. Related and overlapping concepts in the literature include informal accommodation strategies [ 9 ], margin of maneuver [ 10 ], job flexibility [ 8 , 11 , 12 ], adjustability [ 10 ], natural organizational support [ 13 ], and iterative communication-support processes between workers and their supervisors [ 14 , 15 ]. Job flexibility has, in general, been associated with improved quality of working life for employees with chronic disease [ 4 , 11 ], but the concept of job leeway may be especially salient for workers with episodic health problems.…”
mentioning
confidence: 99%